Dual Language Learning / Duale Spracherlernung. Learning German through English - Fee-Alexandra Haase (FahrenHouse, 2014)
In this article we examine the impact of English in the learning process of the German language exemplified with the example of the second language acquisition process of the German language in the programs of German in the Department of Foreign Languages of the University of Nizwa in Oman. This study focuses on the distinct features of students in Oman learning German as a second language in an institution of higher education in Oman. The contrastive rhetoric of a German - Oman Arabic language contact situation is challenging and a unique field of research, which allows us to study the process of foreign language learning (L2) and the implementation of the culture of the native language L1 (Arabic). The reflection of the L1 culture, the Arab Oman culture, in the language learning process of the L2 language (German) will be described, analyzed and discussed aiming the improvement of the L2 learning process. This article investigates into the process of learning German in an Arabic country of native speakers of Arabic from the perspective of the cultural differences of both cultures in terms of their linguistic prepositions. Received: 17/09/2013 / Accepted: 23/11/2013 How to reference this article Haase, F-A. (2014). Dual Language Learning / Duale Spracherlernung. Learning German through English. Foro de Educación, 12(17), pp. 197-216. doi: http://dx.doi.org/10.14516/fde.2014.012.017.010